2019
DOI: 10.1073/pnas.1906824116
|View full text |Cite
|
Sign up to set email alerts
|

Activation loop dynamics are controlled by conformation-selective inhibitors of ERK2

Abstract: Conformational selection by small molecules expands inhibitory possibilities for protein kinases. Nuclear magnetic resonance (NMR) measurements of the mitogen-activated protein (MAP) kinase ERK2 have shown that activation by dual phosphorylation induces global motions involving exchange between two states, L and R. We show that ERK inhibitors Vertex-11e and SCH772984 exploit the small energetic difference between L and R to shift the equilibrium in opposing directions. An X-ray structure of active 2P-ERK2 comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 39 publications
2
79
0
Order By: Relevance
“…However, when ERK2 acquires inhibitor-resistant mutations, such as Y36H and G37C, the inhibitors no longer exhibit enzyme inhibition. Both the inhibitors bind to the ATPbinding pocket of ERK2 (Chaikuad et al, 2014;Pegram et al, 2019). In the ERK2-inhibitor complex structure, the core regions of both the inhibitors (Figure 4) were bound to the central region of the ATP-binding pocket where the adenosine base of the ATP molecule is positioned, and extension 1 and 2 regions interact with peripheral regions of the pocket.…”
Section: Inhibitor Resistance Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when ERK2 acquires inhibitor-resistant mutations, such as Y36H and G37C, the inhibitors no longer exhibit enzyme inhibition. Both the inhibitors bind to the ATPbinding pocket of ERK2 (Chaikuad et al, 2014;Pegram et al, 2019). In the ERK2-inhibitor complex structure, the core regions of both the inhibitors (Figure 4) were bound to the central region of the ATP-binding pocket where the adenosine base of the ATP molecule is positioned, and extension 1 and 2 regions interact with peripheral regions of the pocket.…”
Section: Inhibitor Resistance Mechanismmentioning
confidence: 99%
“…ERK remains inactive until two amino residues within the activation loop are phosphorylated by mitogen-activated kinase (MEK) in response to extracellular growth factors. The ERK signaling pathway is involved in regulating cell proliferation, differentiation, and survival (Chaikuad et al, 2014;Goetz et al, 2014;Tong and Seeliger, 2015;Jaiswal et al, 2018;Pegram et al, 2019;Smorodinsky-Atias et al, 2020). It has been found that the tumor is resistant to ERK inhibitor treatment when the patient is continuously administered a small molecule inhibitor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only that Erks are incapable of autophosphorylation as opposed to most ePKs, several other structural features also distinguish them from common ePKs. For example, although, like most ePKs, Erks seem to reside in equilibrium between two conformations (termed L and R; [74]) these conformations differ from the classical active and inactive conformations of ePKs. For example, no conformational change in the DFG motif (from 'out' to 'in') is apparent in the structure.…”
Section: Erk Activation Is Achieved By Dual Phosphorylation Of a Tey mentioning
confidence: 99%
“…shERK1 knockdown had little or no effect in both cases, suggesting that this is an ERK2-specific event. Next, we repeated this experiment with two ERK2 kinase inhibitors, AZD0364 and SCH772984 37,38 . Cell viability data showed that both AZD0364 and SCH772984 significantly reduced the viability of KRAS G12D mutant GSU cells, but their inhibitory effects were significantly reduced by TP53 gene knockout (Figure 5b).…”
Section: Erk2 Inhibition Which Mimics Trametinib Treatment Promotesmentioning
confidence: 99%